Covremennye metodiki biomekhanicheskikh izmerenii: Kompyuterizirovannyi dinamometricheskii kompleks - Dyshko, B. A. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The purpose of this study was to elaborate a package of applied programs (software) to estimate athletes' abilities to vault biomechanically. Computerized dynamometrical complex was used during the research. The complex was built up on the base of the modified dynamometrical platform PD 3M, made by VISTI. The most popular vaulting tests in coaches' practice were included in the programs package: jump up, serial jumps, drop-test. It was noted by the author, that the computerized dynamometrical complex equipped with specially designed software can help to minimize the results processing time per each probationers group and to accomplish the biomechanical measurements more effectively.